Revitalizing Local Culture in Nusantara Music - Putra, Irdhan Epria Darma; Wimbrayardi, Wimbrayardi; Ferdian, Robby (Gondang: Jurnal Seni dan Budaya, 2023)
Revitalization is a systemic process and methodology to reactivate local potentials in the context of preserving important cultures in the face of changing times. Revitalization of local culture as a big job, not just an activity to explore the heritage of tradition and then preserve it. Rather, that local culture stored in cultural heritage is used as a light in accompanying and coloring the musical character of the nation. Change can only be through real activities and not discourse, "this is where creativity and cultural values that can build human character lie. The collapse of traditional culture is not impossible that the Indonesian nation will lose its identity in the future. The degradation of the younger generation's interest in learning about their local culture must be resolved immediately.